SISTEM PAKAR TROUBLESHOOTING KERUSAKAN PERANGKAT KERAS DAN PERANGKAT LUNAK KOMPUTER - Sullivan Sullivan; Chairisni Lubis (Jurnal Ilmu Komputer dan Sistem Informasi, 2015)
This Application is created to diagnose problem of Personal Computer’s Hardware and Software with Certainty Factor, which User will have to input Symptoms that the user have. The Symptoms will be process using Certainty Factor. Certainty Factor method give accuracy about 95%.  Key words Certainty Factor, Gejala kerusakan Komputer,  Sistem pakar.